Distribution, classification, petrological and related gochemical (SRA) characteristics of a tropical lowland peat dome in the Kota Samarahan-Asajaya area, West Sarawak, Malaysia - Zulkifley, M.T.M.; Fatt, N.T.; Abdullah, W.H.; Raj, J.K.; Paramanathan Param, S.; Hashim, Roslan; Ashraf, M.A. (2013)
Petrographic studies indicate that lateral variations in the decomposition levels of peat are associated with the predominantly occurring peat macerals. Source Rock Analyzer (SRA) results indicate lateral variation in peat organic matter types from type II to III and back again to type II, occurring laterally within the top 0-m to 0.5-m layer at the basin margin to the midsection and further towards the near-center areas of the peat dome. This variation is most likely caused by a combination of factors: (a) Horizontal zonation and lateral variation of the dominant species of plant assemblages (b) Fibric (marginal) peats and hemic to sapric peats associated with type II organic matter (kerogen). Sample organic matter (coal-equivalent kerogen) typing indicates that the relative abundance of phytoclasts and palynomorphs generally supports the organic matter classification obtained by the SRA method. Lateral variations in the peat organic matter types may support the lateral vegetation variation concept. The classification of peat organic matter types (interpreted from visual analyses of palynological slides) occurring from the basin periphery to the mid-section and further towards the basin center yields organic matter of type II to type III and mixed types II to III (coal kerogen-equivalent), respectively.